Jean Rouch raconte a Pierre-Andre Boutang - Boutang, Pierre-Andre (France, 1992)
In conversation with Pierre-Andre Boutang (responsible for the programming at Arte and documentary director himself), Rouch tells about his life and ethnographic envolvement, starting from his first trip to Nigeria. The director of 120 films, he shares his philosophy of life and cinema.
Keywords: France